2006
DOI: 10.1128/jvi.00209-06
|View full text |Cite
|
Sign up to set email alerts
|

High Pathogenicity of Wild-Type Measles Virus Infection in CD150 (SLAM) Transgenic Mice

Abstract: Measles virus (MV) infection causes an acute childhood disease, associated in certain cases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 53 publications
3
53
0
Order By: Relevance
“…CD46 transgenic mice (7, 20, 33, 39, 44), however, may not be suitable for the analysis of MV pathogenesis because CD46 acts as a receptor only for MV vaccine strains and not for most viruses in measles patients (40). Two groups produced SLAM transgenic mice using human SLAM cDNA driven by nonauthentic promoters and showed that MV could infect these mice (16,17,46). However, the expression profiles of SLAM are not natural in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…CD46 transgenic mice (7, 20, 33, 39, 44), however, may not be suitable for the analysis of MV pathogenesis because CD46 acts as a receptor only for MV vaccine strains and not for most viruses in measles patients (40). Two groups produced SLAM transgenic mice using human SLAM cDNA driven by nonauthentic promoters and showed that MV could infect these mice (16,17,46). However, the expression profiles of SLAM are not natural in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…The constructs for SLAM and nectin 4 were commercially acquired. Anti-MV hemagglutinin cl.55 neutralizing antibody, which blocks interaction between H and CD150, has been previously described (43)(44)(45).…”
Section: Plasmids and Reagentsmentioning
confidence: 99%
“…Sera were taken from infected mice at the end of the protocol by intracardiac puncture in EDTA Vacutainer tubes and tested for anti-MV antibodies by ELISA as previously described (45). Briefly, MV nucleoprotein obtained from baculovirus-infected insect cells and purified was coated onto 96-well ELISA plates overnight (1 g/well).…”
Section: Plasmids and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transgenic or knock-in mice expressing human SLAM or CD46 have been generated as small animal models for measles (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). To facilitate MV replication, these mice usually have to be made defective in IFN signaling (16,(18)(19)(20) or used when they are newly born (15,17). Similarly, when human SLAM or CD46 is expressed by transfection, rodent cells become susceptible to MV, but do not allow MV growth as efficiently as primate cells (14,26).…”
mentioning
confidence: 99%